2018
DOI: 10.1007/s00253-018-8786-y
|View full text |Cite
|
Sign up to set email alerts
|

The use of extracellular DNA as a proxy for specific microbial activity

Abstract: The ubiquity and relevance of extracellular DNA (exDNA) are well-known and increasingly gaining importance in many fields of application such as medicine and environmental microbiology. Although sources and types of exDNA are manifold, ratios of specific DNA-molecules inside and outside of living cells can give reliable information about the activity of entire systems and of specific microbial groups or species. Here, we introduce a method to discriminate between internal (iDNA), as well as bound and free exDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 50 publications
1
79
1
Order By: Relevance
“…Applying such a sequential extraction, next to providing exDNA, increases the total amount of not only extractable soil DNA but also that of iDNA (e.g. Ascher et al 2009b; Nagler et al 2018; Wagner et al 2008). …”
Section: Methodological Considerations With Exdna Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Applying such a sequential extraction, next to providing exDNA, increases the total amount of not only extractable soil DNA but also that of iDNA (e.g. Ascher et al 2009b; Nagler et al 2018; Wagner et al 2008). …”
Section: Methodological Considerations With Exdna Extractionmentioning
confidence: 99%
“…Consequently, a ratio of both DNA fractions (exDNA:iDNA) might provide a reliable approximate measure for microbial activity in soils and other environments (Gómez-Brandón et al 2017a, b; Nagler et al 2018). Surprisingly, the activity of different microbes was found to not correlate perfectly with the ratio of exDNA:iDNA but could best be tracked measuring exDNA amounts without relation to iDNA (Nagler et al 2018). These results suggested that exDNA is released by microorganisms proportional to their activity.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pellet and filter were combined and processed for genomic DNA using a MoBio PowerWater DNA Isolate Kit (MoBio, Vancouver, CA) modified by adding a heating step during cell lysis. Total genomic DNA was fluorometrically measured (Quant-iT dsDNA Assay Kit, ThermoScientific, Waltham, MA), and used as proxy for total microbial biomass (Baas et al 2015, Nagler et al 2018). The samples were amplified, targeting the V4 hypervariable region of the bacterial 16S rRNA gene (515-F/806-R, Caporaso et al 2011), and sequenced with Illumina MiSeq (PE 150bp; V2 chemistry) at the Environmental Sample Preparation and Sequencing Facility (ESPSF) at Argonne National Laboratory.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, specific microbial activities have not been taken into consideration. As an estimate, the ratio of intra-/extra-cellular DNA might be used (Nagler et al 2018), as DNA is considered to be a major component of the extracellular polymeric substances (EPS) in biofilms (Flemming and Wingender 2010). This information might strengthen the allocation of main TEA degradation to the biofilms in the CLC and should be considered in future experiments.…”
Section: Resultsmentioning
confidence: 99%